OPTIC USE IN ACCESS NETWORKS - Emil Sarajlija (STED Journal, 2019)
With the development of computer technologies, the need for data transfer is requiring a constant expansion of the data transmission and communication channels. The expansion of the Internet has led to the integration of various communication services such as, video communication, radio, TV. By doing so, a large amount of data was generated. In the beginning, the transmission media were copper cables that supported the transmission of relatively small amount of traffic, while today, optical fiber cables are gaining their spot. The purpose of optical communication systems is the transmission of signals at high speeds over long distances, through optical connections. Unlike the active components on the operator’s side, the user requires only passive elements to establish an optical network. The development of optic led to division of the distance of the optical topology, and FTTx appeared.